Legal Responsibility of Land Maker Offices (PPAT) for Loss of First Sheet of Act - Wulan, Sri; Hasrul, Muh; Arisaputra, Muh Ilham (Fakultas Hukum Universitas Widya Mataram, 2022)
Land Deed Official (PPAT) is a public official who is given the authority to make an authentic deed for certain legal actions in the form of land rights or property rights over flat units. A PPAT is obliged to properly keep the first sheet of the deed he made. However, there is no rule regarding how the PPAT is responsible for the loss of the first sheet of the deed, because the storage of the first sheet is part of the PPAT protocol. The type of research is empirical legal research, the research location is in Makassar City. Data collection techniques are interviews and literature studies. Analyzed qualitatively and presented descriptively. The results of the study indicate that (1) PPAT's responsibility for the loss of the first sheet of the deed due to his mistake is to make a statement that it is true that there has been a transfer of rights from the seller to the client before the PPAT. Then the register book is photocopied and legalized, and so on. (2) Legal remedies by clients who are harmed due to the loss of the first sheet of deed due to PPAT's mistake are to file a complaint of violation by PPAT, the complaint is submitted in writing to the Ministry or through the complaint website, report application or other complaint facilities provided by the Ministry. The client can also submit a report to the MPPD by including the identity of the complainant and the reported party and attaching evidence Keywords: Deed; PPAT; Responsibility